Bridging the Conceptual Gap Between Law and Morality: A Critical Response to H.L.A. Hart’s The Concept Of Law - Kaila Morin (UCL Journal of Law and Jurisprudence, 2011)
In The Concept of Law, H.L.A. Hart develops his theory for a concept of law that rejects the possibility of a necessary connection between law and morality i.e., what the law is from what the law ought to be. He admittedly does so for moral reasons. If there is a conceptual gap between law and morality, it is possible to use the latter as a critical standard for assessing the law by questioning 'is this law too iniquitous to obey or apply?' However, this concept of law is flawed. If the human capacity for moral reason can be used to correctly identify and disobey legally valid though morally deplorable laws, one must assume that belief in what the law ought to be is an inherently moral aspect of the internal point of view. Furthermore, unless one chooses to acknowledge the suppositions of command theory-that is, that law is nothing more than habitual congruencies or the command of a supreme sovereignone must assume Hart's idea of the ultimate rule of recognition as an external statement of fact relating to societies internal perspective of what ought to be. In this way, the inclusion of the internal perspective as a necessary aspect of law entails a connection between law and morality. Otherwise, what law is and what law ought to be become synonymous under a merely external viewpoint. This does not reflect the reality of how individuals assess the law or their actions in relation to the law. Read more